Simulação e avaliação de comportamentos em sistemas multi-agentes baseados em modelos de reputação e interação - Pinto, Andrio dos Santos (Universidade do Vale do Rio do Sinos, 2008)
This work was developed in the context of human behavioral simulation and group interaction study. Our main goal was to propose, to study, to simulate and to evaluate a cooperative multi-agent model based on Interaction and Reputation models. This Master Thesis aims to study and discuss about: (1) questions related to multi-agent systems concerning reputation, agents grouping and relationships between agents (cooperation, betray, trust); (2) the adoption of the simulated IPD (Iterated Prisoner’s Dilemma – a classical problem studied in Game Theory) as a tool for agents’ behavior analysis, which act individually or in groups; (3) a behavioral agent model that includes attributes and properties, as for example, reasoning about reputation, personality and ability to influence (or be influenced) by other agents; (4) the agent x agent interaction, considering different agent behaviors, analyzing the impact of their behaviors when faced to the Iterated Prisoner’s Dilemma problem. In this work we propose an experime
Keywords: grupos humanos virtuais; interação; simulação de comportamentos; avaliação de comportamentos; reputação; sistemas multi-agentes; Ciências Exatas e da Terra